Education in the prevention of STD with family of auditory deficiency carrier - Barroso, Maria Grasiela; Aguiar, Maria I.F.; Oliveira, Keila F. (Brazilian Journal of Sexually Transmitted Diseases, 2001)
The nursing is present in ail care human. ln the people's carriers of auditory deficiency case, there aren't education services with views in the promotion of the youths' health, mainly in the sexuality aspect. Objcctive: lt was objeclified to investigate among people of the family of faulty auditory knowledge on STD/Sida, as well as to socialize information. Methods: The methodology based on the practical research, that has in fact as purpose the social intervention. The research was developed in the period of August/1999 to July/2000, being accomplishe deight group meeting, li was used as suppon a questionnaire applied for 15 companions of the faulty ones of Deaf at lnstitute From Ceará of Education in Fortaleza-CE. Results: The results showed that the companions affirmed not 10 talk wilh its adolescem relatives on the subject. Conclusions: lt was noticed during lhe educational interventions that the companions became more and more able to review orienlations on STD 10 its adolescent relatives.